Addressing diversity dynamics in group therapy : clinical and training applications - Abernethy, Alexis D. (Alexis Deanne), 1958- (New York, NY : Routledge, 2025)
"This book illustrates group dynamics and group interventions in response to diversity-related content and processes in group therapy. Perspectives informed by conceptual frameworks guide the discussion of specific clinical interventions and the implications for training. Cultural dimensions of race, international heritage, classism, religion, and aspects of intersectionality associated with these dimensions are a particular emphasis. Key sections for each chapter include Conceptual Framework, Group Interventions, Teaching or Case Examples, Intersectionality, Ethical Considerations, and Implications for Training and/or Practice. Professional development opportunities for mental health professionals as well as training implications for psychiatry residents and psychology interns is addressed, and case studies offer practical examples for guiding therapists and trainees to intervene more effectively in addressing diversity dynamics in group therapy. An important and timely resource that belongs in every group practitioner's repertoire, this resource is broad enough to be integrated into a course for a training or graduate program and specific enough to serve as a shelf reference for those in practice"--
Keywords: Group psychotherapy; Minorities -- Psychology; Minorities -- Mental health; Intersectionality (Sociology); PSYCHOLOGY / Psychotherapy / Group